Talaromyces halophytorum sp. nov. Isolated from Roots of Limonium tetragonum in Korea - Young-Hyun You; Md. Aktaruzzaman; Inbeom Heo; Jong Myong Park; Ji Won Hong; Seung-Beom Hong (Mycobiology, 2020)
Talaromyces halophytorum sp. nov. was isolated from the roots of halophyte Limonium tetragonum collected from Seocheon-gun, Korea in November 2015. It showed a slow growth on yeast extract sucrose agar at 25 °C, no growth at 4 °C or 37 °C and produced smooth-walled and globose to sub-globose conidia. T. halophytorum is phylogenetically distinct from the other reported Talaromyces species of section Trachyspermi based on multi-locus sequence typing results using partial fragments of β-tubulin, calmodulin, ITS, and RNA polymerase II genes.